Cows grazing above Owl Creek Valley - Sprague, Sallie, photographer (Colorado State University. Libraries, 2008)
Cattle on hillside above eroded bank of upper Owl Creek on the SGS.
Keywords: vegetation; SGS; cattle; landscapes